Case report: Supratherapeutic tacrolimus concentrations with nirmatrelvir/ritonavir in a lung transplant patient: a case report using Rifampin for reversal - Xiong, Yu; Wang, Xiaoxing; Li, Shu; Zhang, Qian; Guo, Lijuan; Chen, Wenhui; Zhao, Zhixia; Liu, Lihong (Frontiers in Pharmacology, 2023)
Paxlovid (nirmatrelvir/ritonavir) is an antiviral drug used to treat COVID-19, nirmatrelvir, a SARS-CoV-2 main protease inhibitor, works by inhibiting viral replication in the early stages, and ritonavir is a strong cytochrome P450 (CYP) 3A inhibitor that helps the nirmatrelvir reach and maintain the therapeutic concentrations. Paxlovid has a potential risk of drug interaction by elevating the plasma concentration of other drugs metabolized by CYP3A, like tacrolimus. This report examines the case of a 57-year-old female lung transplant patient self-administered Paxlovid for 5 days without discontinuing tacrolimus. She presented to the hospital with symptoms of headache, dizziness, palpitations, abdominal distension, nausea, vomiting, and diarrhea. The patient presented with tacrolimus toxicity and the blood concentration of tacrolimus was measured at 106 ng/mL. Urgent medical intervention was initiated, and Rifampin was administered to induce enzyme activity and rapidly decrease the concentration of tacrolimus. By adjusting the tacrolimus dosage, the final concentration was brought within the appropriate range. Clinical pharmacists should prioritize medication education for transplant patients to prevent severe drug interactions and minimize the impact on the patient’s overall well-being.